2013
DOI: 10.1162/adev_a_00015
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Firms and Indigenous Technology Development in the People's Republic of China

Abstract: The People's Republic of China (PRC) is currently promoting indigenous technology development through support of Chinese firms and, arguably, by restricting operations of foreign multinational firms. This policy seems to overlook the impact of foreign firms on technology development in local firms. For instance, technology might leak out to local firms though spillovers. Moreover, competition from foreign firms might force local firms to engage in technology development. We examine the impact of foreign direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Over time FDI to China has changed, moving away from low-tech manufacturing to more technology-intensive activities. Nevertheless there remain restrictions on the operations of MNEs in China (Sjoholm and Lundin 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Over time FDI to China has changed, moving away from low-tech manufacturing to more technology-intensive activities. Nevertheless there remain restrictions on the operations of MNEs in China (Sjoholm and Lundin 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, when intangibility gap is large, it creates a barrier for local firms to absorb advanced knowledge from foreign firms. Several studies have suggested that the relationship between competition and innovation can be nonmonotonic (Aghion, Harris, Howitt, & Vickers, 2001; Boone, 2001; Sjöholm & Lundin, 2013). However, even given this theoretical progress, existing studies have not systematically investigated the coopetitive relationships between local and foreign firms in terms of how intangibility gap affects local firms’ innovation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese banks, represented by Bank of China, occupy a major market share in traditional business areas such as RMB cross-border settlement and payment clearing. They have played a major role in the internationalization of RMB and established a comparative advantage [3][4].…”
Section: Introductionmentioning
confidence: 99%